THE ROLE OF ARTIFICIAL INTELLIGENCE IN MARKETING RESEARCH - Gulnoza Nasrullaeva (European Science Publishing, 2025)
This in the article marketing research artificial intellect technologies importanc, application and results illuminated. Market in the economy competitiveness supply , consumer needs determination and marketing strategies effective in formation artificial of intellect caught place analysis Amazon, Netflix, Sephora , etc. large companies experience The real impact of SI technologies through open Digital is also available in Uzbekistan . trade, banking and tourism in the fields artificial from the intellect use trend increasing The article also discusses the development of SI technologies. advantages and disadvantages and future development prospects seeing Research content analysis, statistics and comparison methods through take gone.
Keywords: Marketing, artificial intelligence, marketing research, big data, machine learning, sentiment analysis, segmentation, recommendation systems, digital transformation, consumer needs, personalization, data security, real-time marketing, uzum market.